Influence of polymer on the surface quality and microstructure in a novel additive manufacturing method using metal paste - Heng, Weicheng; Aoyagi, Kenta; Chiba, Akihiko (Materials letters, 2023)
•Polymer-containing metal paste was used in a new additive manufacturing technology.•0.5–1% polyvinyl alcohol produced a smoother surface both before/after laser melting.•Possible roles of the polymer during deposition and melting are discussed. A new additive manufacturing method using metal paste was developed, in order to reduce waste caused by powder recycling in conventional powder bed fusion and maintain a high density in the fabricated parts. The paste was composed of metal powder, polymer particles, and a volatile solvent. Experiments were conducted to investigate the influence of a low polymer content on the paste during processing, surface topology before and after melting, and microstructure of the single-layer samples. The results showed that polymer addition could prevent the formation of powder clots by improving homogeneity of the metal paste and suppressing defect generation. The polymer also led to a smoother surface by reducing the spatter size. Finer grains were observed in the sample produced at higher polymer content.